Memperkenalkan Entrepreneur di Bidang Peternakan pada Anak Usia Dini di SDN Bukor 1 Bondowoso - Tisya Nadia Pascha; Nauval Yasir; Javan Hayfa Cornain; Theofanus Venard Damara; Rafly Maulana Akbar; Eistifani Fajrin; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Animal husbandry plays a strategic role in supporting food security and meeting the nutritional needs of communities, making it essential to introduce the subject from primary school age. This study aims to measure the increase in students' knowledge and motivation towards animal husbandry through interactive game-based education at SDN Bukor 1 Bondowoso. The research employed a pre-experimental one-group pretest-posttest design involving 29 students in grades 3 and 4, conducted over three sessions through educational games, group discussions, and simple practices. Measurements were taken using pre-test and post-test instruments, which were analyzed descriptively to observe changes in students' understanding. The results showed an increase in students' comprehension, marked by a rise in the percentage of scores of 75-100 from 7% in the pre-test to 76% in the post-test, as well as a decrease in scores of 0-55 from 62% to 3%. These findings indicate that interactive game-based education is effective in improving primary school students' knowledge and motivation regarding animal husbandry and can serve as an alternative contextual learning approach suitable for children's characteristics.